Regiospecific Plasmonic Assemblies for in Situ Raman Spectroscopy in Live Cells. - Liguang Xu; Hua Kuang; Chuanlai Xu; Wei Ma; Libing Wang; Kotov, Nicholas A. (Journal of the American Chemical Society, 2012)
Multiple properties of plasmonic assemblies are determined by their geometrical organization. While high degree of complexity was achieved for plasmonic superstructures based on nanoparticles (NPs), little is known about the stable and structurally reproducible plasmonic assemblies made up from geometrically diverse plasmonic building blocks. Among other possibilities, they open the door for the preparation of regiospecific isomers of nanoscale assemblies significant both from a fundamental point of view and optical applications. Here, we present a synthetic method for complex assemblies from NPs and nanorods (NRs) based on selective modification of NRs with DNA oligomers. Three types of assemblies denoted as End, Side, and Satellite isomers that display distinct elements of regiospecificity were prepared with the yield exceeding 85%. Multiple experimental methods independently verify various structural features, uniformity, and stability of the prepared assemblies. The presence of interparticle gaps with finely controlled geometrical parameters and inherently small size comparable with those of cellular organelles fomented their study as intracellular probes. Against initial expectations, SERS intensity for End, Side, and Satellite isomers was found to be dependent primarily on the number of the NPs in the superstructures rationalized with the help of electrical field simulations. Incubation of the label-free NP-NR assemblies with HeLa cells indicated sufficient field enhancement to detect structural lipids of mitochondria and potentially small metabolites. This provided the first proof-of-concept data for the possibility of real-time probing of the local organelle environment in live cells. Further studies should include structural optimization of the assemblies for multitarget monitoring of metabolic activity and further increase in complexity for applications in transformative optics.